A busca da coerência: reflexões sobre a produção do GT Educação Popular - Regina Garcia Leite (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
This texts sets out to problematise recurrent questions in the production of the Working Group on Popular Education: amorosity, autopoiesis, process of auto-eco-organisation; new organisation based on chaos time/ clock and time/collective interest; in defence of slow men; a sociology of slow history the relation practice/ theory/practice; the epistemological reflection on who, how and where knowledge is produced; the second epistemological rupture which brings science and common sense closer together again; the auto-reflexive dimension of the epistemological question the arrival of outsiders in research in popular education the doubt which leads to the discovery of the new the crisis of understanding is ours those who do not see because they do not understand; the acceptance of the other as a condition for self-acceptance; understanding understanding rewriting history from the point of view of the subordinate; narratives lost in official history; oral discourse; the hegemony of a logic which silences the logics of daily life; popular religiosity shared responsibility; solidarity of concerns. And the challenge which remains is if the Working Group on Popular Education repudiates the ranking of knowledge as a means of exercising power, if it recognises plural forms of culture giving rise to visions of the world which contain different logics, how do the group members begin to construct a curriculum in their pedagogical actions, either inside or outside the school, or rather, how do their political-pedagogical practices change?